2017
DOI: 10.1111/cpr.12367
|View full text |Cite
|
Sign up to set email alerts
|

Cellular behaviours of bone marrow‐derived mesenchymal stem cells towards pristine graphene oxide nanosheets

Abstract: Pristine GO nanosheets at a concentration of 0.1 μg/mL provide benefits to promote BMSCs proliferation and osteogenesis under a sequential-seeding method, contributing to the use of GO for dental implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
55
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 46 publications
(45 reference statements)
5
55
3
Order By: Relevance
“…2,3 However, the majority of the work only focuses on the biological effects of nanomaterials while their intrinsic immunomodulatory effects are often neglected. [4][5][6] Take the bone implant materials: for example, titanium (Ti) metal is extensively used in clinical practice due to its outstanding osseointegration ability. Recently, the influence of Ti implant on macrophage adhesion and the effects of macrophage activation on osseointegration have been noticed.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 However, the majority of the work only focuses on the biological effects of nanomaterials while their intrinsic immunomodulatory effects are often neglected. [4][5][6] Take the bone implant materials: for example, titanium (Ti) metal is extensively used in clinical practice due to its outstanding osseointegration ability. Recently, the influence of Ti implant on macrophage adhesion and the effects of macrophage activation on osseointegration have been noticed.…”
Section: Introductionmentioning
confidence: 99%
“…The most dominant cell types used in the included articles were mesenchymal stem cells (MSCs), including human adipose-derived stem cells (hADSCs), [17][18][19][20][21][22] Goat ADSCs, 23 human dental pulp stem cells (hDPSCs), 24 human alveolar bone marrow stem cells (hABMSCs), 25 human periodontal ligament stem cells (hPDLSCs), 26,27 and bone MSCs (BMSCs), [28][29][30][31] such as human BMSCs 19, 32-41 (hBMSCs), murine BMSCs (mBMSCs), 4, 42-49 rabbit BMSCs (rBMSCs), 50 murine MSCs cell line C3H10T1/2 51,52 and Caprine BMSCs (cMBSCs). 53 The type of the MSCs in fifteen studies 19,32,36,40,[54][55][56][57][58][59][60][61][62][63][64] was not defined.…”
Section: Cell Sourcesmentioning
confidence: 99%
“…CharacterizationSynthesized graphene, graphene derivatives and their compositions were chemically characterized using Fourier-transform infrared (FTIR)14, 21, 30, 36, 37, 42, 43, 45, 48, 61, 63, 65, 66, 68, 73 74, 75, 84-86, 91, 92 and raman spectroscopy.13, 17-19, 21, 22, 24-28 32-34, 36, 37, 40-42, 45, 47, 48, 54, 55, 57, 59, 61-65, 68, 69, 71, 72, 75-78, 86-89, 93 Also, morphology and topography of the samples were characterized by SEM,4, 13, 20-23, 25, 26, 29, 33-36, 38, 43, 45-56, 58, 60, 61, 63, 65, 66, 70, 71 73-85, 87, 91, 92 field emission scanning electron microscope (FESEM),17,40,42,44,72,79,86,90,91 transmission electron microscopy (TEM),4,18,30,31,43,44,50,53,61,64,66,71,77,80,82,86,87,[89][90][91][92][93][94] and atomic force microscope (AFM).14, 17-19, 21, 24-26, 36-40, 42, 45, 47, 49, 53, 54, 59, 62 69, 70, 77, 79, 80, 82, 89 Surface hydrophobicity of the composites and their chemical environments were evaluated by contact angle (CA) measurements14, 20, 28, 36-38, 41, 42, 46, , 70, 78, 81, 86, 88, 91, 92 were employed in the various studies to evaluate mechanical strength. Inductively coupled plasma atomic emission spectrometry (ICP-AES)…”
mentioning
confidence: 99%
“…Rosa V et al showed that DPSCs were anchored to the rough surface provided by GO, as assessed by scanning electron microscopy (SEM) [26]. Moreover, GO at the concentration of 0.1 lg/ml allowed for BMSC attachment and promoted proliferation, whilst GO at 10 lg/ml was cytotoxic [27]. In a review by Mohammadrezaei D et al, up to 50 lg/ml for GO seems to be safest for most cell lines [25].…”
Section: Introductionmentioning
confidence: 99%
“…In a review by Mohammadrezaei D et al, up to 50 lg/ml for GO seems to be safest for most cell lines [25]. In addition, GO could induce BMSC and DPSC osteogenic differentiation in vitro [26,27]. GO-coated b-tricalcium phosphate scaffold increased the rate of new bone formation in vivo [28].…”
Section: Introductionmentioning
confidence: 99%